Sequences in development in North East India: A study of tradition, continuity and change - Bhattacharjee, J.B. (ed.) (New Delhi Omsons Publications, 1989)
The volume is a collection of papers presented in a seminar on Sequence of Development in North-East India at Shillong organized by NEICSSR in December 1985. The volume is a study in the development processes of the challenge region of North-East India. It traced the stages in development in retrospect, identified the constraints- political, social and environmental and the potentials and suggested the strategies for the future.